Institutional Support and Crony Capitalism: The State of the Philippine Shipping Industry during the period of Authoritarian Rule - Poblador, Karl Friedrik K. (Diliman Review, 2024)
Soon after President Ferdinand E. Marcos proclaimed martial law, institutions were set up to support the development of the shipping industry. Shipping is integral to the overseas and domestic flow of commodities and also had to be developed as a complement to the cash crop economy that was prevalent at that time. At the onset, several presidential decrees were issued in support of the industry. Multilateral lending was also made available to stakeholders in the industry and there was actually a marked improvement as the seventies came to a close. However, several pertinent personalities within the President’s circle undermined that agenda to pursue their own motivations. This included the reckless acquisition of vessels and the breaking up of a colonial-era institution that used to be an integral part of the Philippine maritime industry. As such, major shipping assets went to waste as the economic crisis of the early eighties set in and became part of the Aquino Administration’s agenda of cleaning up the damage done by the Marcos regime.